Factors influencing students' continuance usage intention with online learning during the pandemic: a cross-country analysis. Issue 9 (4th July 2022) - Taghizadeh, Seyedeh Khadijeh; Rahman, Syed Abidur; Nikbin, Davoud; Alam, Mirza Mohammad Didarul; Alexa, Lidia; Ling Suan, Choo; Taghizadeh, Shirin
ABSTRACT : This study aims to identify the factors affecting students' satisfaction with online learning, examine the relationship between satisfaction and continuance usage intention, and explore the direct and moderating role of self-quarantine during a pandemic situation. The research model has been developed based on three theories, namely, Expectation Confirmation Theory, Diffusion of Innovation Theory, and Unified Theory of Acceptance and Use of Technology. Through an online survey, data were collected from 1193 university students from Oman, Iran, Bangladesh, Romania, and Malaysia and analysed using Structural Equation Modelling technique with SmartPLS V.3 software. Results indicated that factors affecting student's satisfaction with an online learning vary in each sample. In all samples, satisfaction significantly influences students' continuance usage intention with the online learning. In some samples, self-quarantine has a direct effect on continuance usage intention and plays a moderating role in Romania sample. The findings contribute to the universities and instructors how online systems factors elevate students' continuance usage intention. The uniqueness of this study is the integration of three theories to obtain research objectives. The details of the results and both theoretical and practical implications have been described in the paper.